AN EXAMINATION OF THE EFFECTS OF MOTIVATION, COMPENSATION, AND CAREER DEVELOPMENT ON THE PERFORMANCE OF BMT EMPLOYEES - Eduard Yohannis Tamaela (STIEKOP MALANG PRESS, 2022)
Purpose – The purpose of this research is to determine the effect of motivation, compensation, and career development on teacher performance at BMT. Design/methodology/approach – The sample size for this study was 51 employees. The statistical tools utilized were Regression Multiple (Multiple Regression) with the sampling approach of simple random sampling. The statistical software SPSS 16.0 was used to examine the data. Findings – The results of this study showed the F test (simultaneous) that motivation, compensation, and career development significantly affected employee performance with a sig F of 0,000 0.1 and an F count value of 18.976. The result of the T-test (partial) motivation significantly affected the performance of teachers with a sig t of 0.025 0.1 and a 2.310 t count, while development significantly affected the performance of employees with a sig t of 0.000 0.1 and a value of 4.439. Research limitations/implications – This research is only conducted in a small area with small sample size and cannot be generated in any other environment. Originality/value – So it can be concluded that motivation, compensation, and career development simultaneously affect the performance of employees, but only partially. Motivation and career development variables affect employee performance. Keywords: Motivation, Compensation, Career, and Performance Paper type: Case Study